2013
DOI: 10.1186/1471-2105-14-90
|View full text |Cite
|
Sign up to set email alerts
|

An improved sequence based prediction protocol for DNA-binding proteins using SVM and comprehensive feature analysis

Abstract: BackgroundDNA-binding proteins (DNA-BPs) play a pivotal role in both eukaryotic and prokaryotic proteomes. There have been several computational methods proposed in the literature to deal with the DNA-BPs, many informative features and properties were used and proved to have significant impact on this problem. However the ultimate goal of Bioinformatics is to be able to predict the DNA-BPs directly from primary sequence.ResultsIn this work, the focus is how to transform these informative features into uniform … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
50
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 69 publications
(51 citation statements)
references
References 67 publications
0
50
0
Order By: Relevance
“…The PSSM, which represents evolutionary information of amino acid sequences, has been used widely in research on the prediction of DNA-binding residues [3035] and DNA-binding proteins [6,14,28] based on sequence information. Compared with other features, PSSM contributes most to improving the prediction performance of DNA-binding residues and DNA-binding proteins.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The PSSM, which represents evolutionary information of amino acid sequences, has been used widely in research on the prediction of DNA-binding residues [3035] and DNA-binding proteins [6,14,28] based on sequence information. Compared with other features, PSSM contributes most to improving the prediction performance of DNA-binding residues and DNA-binding proteins.…”
Section: Methodsmentioning
confidence: 99%
“…During the past few decades, a series of studies on the identification of DNA-binding proteins using sequence information have been published [414]. Machine learning algorithms were employed to construct models to predict DNA-binding proteins and produced effective performances [49,1119].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies [4,22] showed that the overall amino acid composition of 20 standard amino acids was a widely used sequence feature in the field of bioinformatics. In this feature space, the overall amino acid composition is defined as the occurrence frequencies of 20 standard amino acids.…”
Section: Overall Amino Acid Composition (Oaac)mentioning
confidence: 99%
“…Amino acid composition of proteins associated with the biochemical properties are the commonly used sequence-based features, for example Cai and Lin [1] used protein's amino acid composition, limited range correlation of hydrophobicity and solvent accessible surface area to identify DBPs; Ahmad et al [2] found the specificity of sequence level and binding level and analyzed the relationship between them; Fang et al [3] encoded the feature space by autocross-covariance (ACC) transform, pseudoamino acid composition, dipeptide composition; Zou et al [4] adopted three different feature transformation methods to generate numeric feature vectors from protein sequences; Lin et al [5] represented each sequence as pseudo amino acid composition by applied grey model. For more accurately predictive performance, the combinations of different features were employed, for example Kumar et al [6] derived sequence properties by frequency of amino acid, amino acid groups, secondary structure, comAbstract: Identification of DNA-binding proteins is an important problem in biomedical research as DNA-binding proteins are crucial for various cellular processes.…”
Section: Introductionmentioning
confidence: 99%